PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT. BPJS KETENAGAKERJAAN KANTOR WILAYAH DKI JAKARTA - Irawan Noor (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of leadership and communication on the performance of PT. DKI Jakarta Regional Office BPJS Employment. The research method used is descriptive quantitative method using a survey system. The population in this study were employees at PT. DKI Jakarta Regional Office BPJS, totaling 30 employees. Researchers took and used all populations to be sampled using the method of multiple linear regression analysis and simple. The results showed that 1). Together leadership and communication greatly affect the performance of employees at PT. DKI Jakarta Regional Office BPJS Employment, 2). That leadership influences employee performance at PT. DKI Jakarta Regional Office BPJS Employment. 3). The results showed that communication affects the performance of employees at PT. DKI Jakarta Regional Office BPJS Employment.